Insights into the role of cannabis in the management of inflammatory bowel disease. (September 2019) - Picardo, Sherman; Kaplan, Gilaad G.; Sharkey, Keith A.; Seow, Cynthia H.
Over the last decade, interest in the therapeutic potential of cannabis and its constituents (e.g. cannabidiol) in the management of inflammatory bowel diseases (IBD) has escalated. Cannabis has been increasingly approved for a variety of medical conditions in several jurisdictions around the world. In animal models, cannabinoids have been shown to improve intestinal inflammation in experimental models of IBD through their interaction with the endocannabinoid system. However, the few randomized controlled trials of cannabis or cannabidiol in patients with IBD have not demonstrated efficacy in modulating inflammatory disease activity. Cannabis may be effective in the symptomatic management of IBD. Given the increasing utilization and cultural acceptance of cannabis, physicians need to be aware of its safety and efficacy in order to better counsel patients. The aim of this review is to provide an overview of the role of cannabis in the management of patients with IBD.